2021
DOI: 10.3389/fpls.2021.761139
|View full text |Cite
|
Sign up to set email alerts
|

Acceleration of Aril Cracking by Ethylene in Torreya grandis During Nut Maturation

Abstract: Torreya grandis ‘Merrillii’ is a famous nut with great nutritional value and high medicinal value. Aril cracking is an important process for seed dispersal, which is also an indicator of seed maturation. However, the cracking mechanism of T. grandis aril during the maturation stage remains largely unknown. Here, we provided a comprehensive view of the physiological and molecular levels of aril cracking in T. grandis by systematically analyzing its anatomical structure, physiological parameters, and transcripto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 101 publications
0
2
0
Order By: Relevance
“…Ethylene primarily alters cell wall metabolism in the abscission zone through degradation and new synthesis [33,34]. Research has shown that ethylene is associated with PME gene expression [35,36], so we believe that the decreased expression levels of key genes involved in ethylene synthesis result in reduced ethylene production, further reducing the activity of pectinase in the cell wall, delaying pectin degradation, and consequently delaying fruit abscission. However, the mechanisms by which GA 3 and 2,4-D inhibit ethylene synthesis and affect the expression of cell walldegrading enzyme genes in blue honeysuckle fruit are not yet clear and require further experimental validation.…”
Section: Discussionmentioning
confidence: 99%
“…Ethylene primarily alters cell wall metabolism in the abscission zone through degradation and new synthesis [33,34]. Research has shown that ethylene is associated with PME gene expression [35,36], so we believe that the decreased expression levels of key genes involved in ethylene synthesis result in reduced ethylene production, further reducing the activity of pectinase in the cell wall, delaying pectin degradation, and consequently delaying fruit abscission. However, the mechanisms by which GA 3 and 2,4-D inhibit ethylene synthesis and affect the expression of cell walldegrading enzyme genes in blue honeysuckle fruit are not yet clear and require further experimental validation.…”
Section: Discussionmentioning
confidence: 99%
“…Torreya grandis “Merrillii” is a gymnosperm, and a member of the Torreya genus and Taxaceae family ( Gao et al, 2021 ). It is a species of Torreya grandis Fort.ex Lind.…”
Section: Introductionmentioning
confidence: 99%